Empowerment of Chili Business Groups through Processing Centers and Digital Marketing in Banggae Village, Takalar Regency: Pemberdayaan Kelompok Usaha Cabai melalui Pusat Pengolahan dan Digital Marketing di Desa Banggae Kabupaten Takalar - Ahyani Mirah Liani; Asmaul Husnah; Mar Athul Wazithah T; Norma Nasir; Khadijah Khadijah; Abd Hakim (Mattawang: Jurnal Pengabdian Masyarakat, 2026)
Banggae Village, located in Takalar Regency, has considerable natural resource potential, particularly in chili commodities. Chili is one of the agricultural products widely cultivated by the local community and has the potential to be developed into various value-added processed products. However, the utilization of this commodity has not been optimal, as most farmers still sell their harvest in fresh form without further processing. This condition results in relatively low product value and limits the development of community-based businesses related to chili commodities. This community service program aims to enhance the capacity of the community in developing chili-based businesses through the establishment of business groups, the development of a chili processing center, and digital marketing training. The implementation of the program was carried out through several stages, including program socialization, formation of business groups, establishment of a chili processing center as a shared production facility, product packaging training, and digital marketing training using social media and online marketplaces. The results of the program indicate an improvement in the community’s capacity to develop chili-based enterprises. The program successfully established four chili business groups across four hamlets in Banggae Village, namely Jarannika, Banggae, Bolo, and Garassi, with a total of 20 active members. In addition, one chili processing center was established and utilized as a facility for the production and packaging of processed chili products. The training activities were attended by 23 participants, with an average level of understanding reaching approximately 85% based on the evaluation results. Following the program, more than 80% of the participants were able to utilize digital platforms such as TikTok, Instagram, Facebook, Shopee, and WhatsApp as media for product promotion and marketing. This program contributes to improving community entrepreneurial skills and encourages the use of digital technology to expand the market reach of chili-based products derived from local village resources. Abstrak Desa Banggae yang terletak di Kabupaten Takalar memiliki potensi sumber daya alam yang cukup besar, khususnya pada komoditas cabai. Cabai merupakan salah satu komoditas pertanian yang banyak dibudidayakan oleh masyarakat dan memiliki peluang untuk dikembangkan menjadi berbagai produk olahan bernilai ekonomi. Namun, pemanfaatan komoditas tersebut masih belum optimal karena sebagian besar petani menjual hasil panen dalam bentuk segar tanpa melalui proses pengolahan lebih lanjut. Kondisi ini menyebabkan nilai tambah produk menjadi relatif rendah serta peluang pengembangan usaha masyarakat berbasis komoditas cabai belum berkembang secara maksimal. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk meningkatkan kapasitas masyarakat dalam mengembangkan usaha berbasis cabai melalui pembentukan kelompok usaha, pendirian pusat pengolahan cabai, serta pelatihan digital marketing. Pelaksanaan kegiatan dilakukan melalui beberapa tahapan, yaitu sosialisasi program, pembentukan kelompok pelaku usaha, pendirian pusat pengolahan cabai sebagai fasilitas produksi bersama, pelatihan pengemasan produk, serta pelatihan pemasaran digital berbasis media sosial dan marketplace. Hasil kegiatan menunjukkan adanya peningkatan kapasitas masyarakat dalam pengembangan usaha cabai. Program ini berhasil membentuk 4 kelompok usaha cabai yang tersebar di empat dusun di Desa Banggae, yaitu Dusun Jarannika, Banggae, Bolo, dan Garassi, dengan jumlah 20 anggota aktif. Selain itu, telah dibentuk 1 pusat pengolahan cabai yang dimanfaatkan sebagai tempat produksi dan pengemasan produk olahan cabai. Kegiatan pelatihan diikuti oleh 23 peserta, dengan tingkat pemahaman materi mencapai sekitar 85% berdasarkan hasil evaluasi kegiatan. Setelah kegiatan berlangsung, lebih dari 80% peserta mampu memanfaatkan platform digital seperti TikTok, Instagram, Facebook, Shopee, dan WhatsApp sebagai media promosi dan pemasaran produk. Kegiatan ini memberikan kontribusi dalam meningkatkan keterampilan kewirausahaan masyarakat serta mendorong pemanfaatan teknologi digital dalam memperluas jangkauan pemasaran produk olahan cabai berbasis potensi lokal desa.